1998
DOI: 10.1104/pp.116.1.429
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Shock-Induced Changes in Intracellular Ca2+Level in Tobacco Seedlings in Relation to Thermotolerance1

Abstract: Exposure of plants to elevated temperatures results in a complexThe responses of plants to HS have received increasing attention in recent years. Elevated temperatures initiate changes in transcription and selective translation of HS mRNA encoding HSPs, thereby enhancing thermotolerance of treated plants (Nover et al., 1989; Nover, 1991;Vierling, 1991; Howarth and Ougham, 1993;Waters et al., 1996). However, the pathways by which HS signals are perceived and transduced to activate gene expression of HSPs and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
162
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(177 citation statements)
references
References 46 publications
11
162
2
2
Order By: Relevance
“…Another interesting aspect to take into account is the photosynthetic capacity of the plant. It has been reported in literature that ABA stops the photosynthesis of different species under controlled conditions (Daie & Campbell, 1981;Xu et al, 1995;Gong et al, 1998;Wilkinson & Davies, 2002;Reddy et al, 2004;Liu et al, 2005); but our results showed an increase in the content of dry matter that increases in correlation with chlorophyll levels (Travaglia et al, 2009). These results are similar to those we observed during three years of essays with field-grown wheat treated with ABA; the treated plants showed higher levels of chlorophyll and maintained green leaves longer (5 to 10 days) than control plants (Travaglia et al, 2010).…”
Section: Aba Promotes Yield In Field-cultured Soybeansupporting
confidence: 81%
“…Another interesting aspect to take into account is the photosynthetic capacity of the plant. It has been reported in literature that ABA stops the photosynthesis of different species under controlled conditions (Daie & Campbell, 1981;Xu et al, 1995;Gong et al, 1998;Wilkinson & Davies, 2002;Reddy et al, 2004;Liu et al, 2005); but our results showed an increase in the content of dry matter that increases in correlation with chlorophyll levels (Travaglia et al, 2009). These results are similar to those we observed during three years of essays with field-grown wheat treated with ABA; the treated plants showed higher levels of chlorophyll and maintained green leaves longer (5 to 10 days) than control plants (Travaglia et al, 2010).…”
Section: Aba Promotes Yield In Field-cultured Soybeansupporting
confidence: 81%
“…The major limitation of the use of aequorin is low light emission, meaning that imaging even at the subtissue level has proved elusive (Zhu et al, 2013), and subcellular imaging in plants is not possible. Aequorin has found high utility and has identified roles for [Ca 2+ ] cyt signaling in mechanical stimulation, cold, salinity, and pathogen stress and in the daily timing of plants (Campbell et al, 1996;Knight et al, 1996Knight et al, , 1997Gong et al, 1998;Kawano et al, 1998;Baum et al, 1999;Love et al, 2004;Kosuta et al, 2008;Monshausen et al, 2009;Zhu et al, 2013). However, in leaves and shoots, it is not known from which tissues the stress-and circadian-regulated [Ca 2+ ] i signals arise.…”
Section: Camentioning
confidence: 99%
“…However, what is complicated is that H 2 O 2 has been demonstrated to be a signal molecule as well. Along with the observed participation of H 2 O 2 in ABA-induced activities of antioxidant enzyme (Gong et al, 1998;Jiang and Zhang, 2002;Chaves et al, 2009), it is difficult to say which signal is the main induced factor.…”
Section: Interactions Of Aba and Ros In The Regulation Of Cold Toleramentioning
confidence: 99%